전략적 네트워크 추진동기가 기업역량과 운영구조에 미치는 영향에 관한 실증연구 - 정종식(Jeong, Jong-sik); 김현지(Kim, Hyeon-jee) (대한경영학회지, 2006)
본 논문의 목적은 전략적 네트워크 추진동기가 기업역량과 운영구조에 미치는 영향을 실증하는 것으로서, 특히 전략적 집단과 협력전략의 관계를 검증하였다.전략적 네트워크는 내부와 외부에서 일어나는 변화에 따라 기회와 위기를 주기 때문에 기업은 다양한 동기에 따라 참여한다. 또한 그 동기는 제휴를 추진하기 전이나 후에도 영향을 미치기 때문에 본 연구에서는 그 영향을 실증하고 분석하여 시사점을 제시하였다. 특히 전략적 네트워크 추진동기를 시장지배력이론, 거래비용이론, 자원기반관점, 제도이론으로 나누었고, 이것으로 협력관계를 맺는 동기와 협력전략의 관계를 제시하였다. The purpose of this paper is to study the effects of motives driving strategic networks formation on firm's capabilities and operating structures. Especially, By examining the relationship between strategic group membership and cooperative strategies, several factors are identified. Using four salient perspectives, namely market power theory, transaction cost theory, the resource-based view, institutional theory, this paper attempts to provide a theoretical rationale linking motives for the creation of inter-firm cooperative relationships and cooperative strategies. The results provide a valuable tool for managers, stock market experts and strategy researcher analysing competitive and cooperative strategies. KCI Citation Count: 8